Mismanagement of marine fisheries - Longhurst, Alan R. (Cambridge, UK ; New York : Cambridge University Press, 2010)
"Longhurst examines the proposition, central to fisheries science, that a fishery creates its own natural resource by the compensatory growth it induces in the fish, and that this is sustainable. His novel analysis of the reproductive ecology of bony fish of cooler seas offers some support for this, but a review of fisheries past and present confirms that sustainability is rarely achieved. The relatively open structure and strong variability of marine ecosystems is discussed in relation to the reliability of resources used by the industrial-level fishing that became globalised during the 20th century. This was associated with an extraordinary lack of regulation in most seas, and a widespread avoidance of regulation where it did exist. Sustained fisheries can only be expected where social conditions permit strict regulation and where politicians have no personal interest in outcomes despite current enthusiasm for ecosystem-based approaches or for transferable property rights"--Provided by publisher.
Includes Includes.
Includes bibliographical references and index.
Keywords: Sustainable fisheries; Fish populations; Fisheries -- Management